Seroprevalence of Hepatitis B and Hepatitis C Virus among Healthy Blood Donors in Tertiary Care Hospital - Pramanik, SH; Rahman, Abu Shahin Mohammed Mahbubur; Islam, Md Nurul; Rabbani, Md Golam; Rahman, Md Khalilur (TAJ: Journal of Teachers Association, 2018)
Hepatitis B virus (HBV) & Hepatitis C virus (HCV) are transfusion transmissible infections. A study was conducted from September, 2015 to March, 2016 at the Transfusion Medicine Department of Rajshahi Medical College Hospital to determine the prevalence of asymptomatic hepatitis B and C virus in apparently healthy blood donors, were subjected to ELISA for screening of hepatitis B surface antigen and Hepatitis C virus. A total of 200 blood donors were screened, the seroprevalence of HBV & HCV infection was 5.0% & 2.0% respectively. The HBV seroprevalence in male donors was 182/8 (4.4%) and in female donors was 18/2 (11.1%). Four donors were found seropositive for HCV giving a seroprevalence of 2%. HCV seroprevalence in male was 182/4 (2.2%) and no female. Seroprevalence of HCV and HBV were higher in younger donors, service holders, married respondents and middle class donors. To reduce the prevalence of post-transfusion hepatitis and stringent donor screening procedure, routine screening for HBV & HCV in blood banks should be performed using more sensitive methods (ELISA). TAJ 2015; 28(1): 26-31